2009
DOI: 10.1007/s10295-009-0656-2
|View full text |Cite
|
Sign up to set email alerts
|

Cellulases from Penicillium funiculosum: production, properties and application to cellulose hydrolysis

Abstract: The objective of this work is to investigate the utilization of two abundant agricultural residues in Brazil for the production and application of cellulolytic enzymes. Different materials obtained after pretreatment of sugarcane bagasse, as well as pure synthetic substrates, were considered for cellulase production by Penicillium funiculosum. The best results for FPase (354 U L(-1)) and beta-glucosidase (1,835 U L(-1)) production were observed when sugarcane bagasse partially delignified cellulignin (PDC) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 25 publications
7
47
1
3
Order By: Relevance
“…Singh et al (2009) andCastro et al (2010) found that Aspergillus species are the best producers of exo and endoglucanases, and that the concentrations of β-glucosidases produced by species of this genus are particularly high, which may represent an advantage in the process of biomass saccharifi cation.…”
Section: Enzymesmentioning
confidence: 99%
“…Singh et al (2009) andCastro et al (2010) found that Aspergillus species are the best producers of exo and endoglucanases, and that the concentrations of β-glucosidases produced by species of this genus are particularly high, which may represent an advantage in the process of biomass saccharifi cation.…”
Section: Enzymesmentioning
confidence: 99%
“…T. harzianum are frequently reported as control agent against fungal pathogens (Arantes and Saddler 2010;Banerjee et al 2010). However, recent studies have also revealed the potential of this fungus for cellulase production and industrial applications (Ahmed et al 2009;Castro et al 2010aCastro et al , 2010b. Likewise, T. harzianum has also become a promising system for xylanase production under appropriate conditions (Franco et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Glucose concentration was determined usinga kit based on the glucose oxidase assay (Katal®) and total reducing sugar content was determined according to the method described by Miller (1959). The hydrolysis yield was determined using equation described by Maeda et al (2011) from the carbohydrate contents of SCB and PDC previously determined by Castro et al (2010a).…”
Section: Sugarcane Bagasse Hydrolysismentioning
confidence: 99%
“…Among three species of Penicillium, P. funiculosum has industrial applications as it involves in cellulose production (Roberto et al, 2013). Penicillium funiculosum is able to secrete a balanced cellulasic system (Rao et al, 1988;Castro et al, 2010). The existence of P. funiculosum in the plant parts and the insects around the plants was well established (Lim and Rohrbach, 1980).…”
Section: Discussionmentioning
confidence: 99%